Evaluation of the spoilage potential of bacteria isolated from chilled chicken in vitro and in situ. (May 2017) - Wang, Guang-yu; Wang, Hu-hu; Han, Yi-wei; Xing, Tong; Ye, Ke-ping; Xu, Xing-lian; Zhou, Guang-hong
Abstract: Microorganisms play an important role in the spoilage of chilled chicken. In this study, a total of 53 isolates, belonging to 7 species of 3 genera, were isolated using a selective medium based on the capacity to spoil chicken juice. Four isolates, namely Aeromonas salmonicida 35, Pseudomonas fluorescens H5, Pseudomonas fragi H8 and Serratia liquefaciens 17, were further characterized to assess their proteolytic activities in vitro using meat protein extracts and to evaluate their spoilage potential in situ . The in vitro studies showed that A. salmonicida 35 displayed the strongest proteolytic activity against both sarcoplasmic and myofibrillar proteins. However, the major spoilage isolate in situ was P. fragi H8, which exhibited a fast growth rate, slime formation and increased pH and total volatile basic nitrogen (TVBN) on chicken breast fillets. The relative amounts of volatile organic compounds (VOCs) originating from the microorganisms, including alcohols, aldehydes, ketones and several sulfur compounds, increased during storage. In sum, this study demonstrated the characteristics of 4 potential spoilage bacteria on chilled yellow-feather chicken and provides a simple and convenient method to assess spoilage bacteria during quality management. Highlights: Specific spoilage bacteria were identified using raw-chicken juice agar (RJA). Aeromonas salmonicida 35 showed the strongest spoilage potential in vitro . Pseudomonas fragi H8 showed the strongest spoilage potential in situ . The RJA assay may serve as a convenient method to assess potential spoilage bacteria.